Development of Learning Media Based on Arduino Load Cell on Pascal’s Law Topic to Improve Students’ Learning Outcomes - Fian Rifqi Irsalina; Firda Fikri Andini; Dadi Rusdiana (Jurnal Pendidikan Fisika, 2025)
Observations in several high schools in Bandung City show that students struggle to grasp Pascal's Law due to the absence of concrete visual representations. A preliminary survey involving 72 grade XI students from two schools revealed that only 45% could correctly explain the fundamental concept of Pascal's Law, and around 65% showed a lack of interest in physics, mainly because they found the material too complex. This study aims to develop Arduino Load Cell-based learning media to enhance students' comprehension of Pascal's Law. Using a Research and Development (R&D) approach with the ADDIE model, the study included five phases: analysis, design, development, implementation, and evaluation, with seven grade XII students as participants. The research utilized validation sheets, practicality questionnaires, student feedback forms, and pre-and post-tests. The findings indicated that the learning media exhibited a remarkably high degree of validity and practicality. The students' responses to this media were predominantly favorable, particularly with regard to the benefits it provided. Analysis of learning outcomes showed N-Gain scores ranging from moderate to high, signifying a notable improvement in student understanding. These results underscore the need for interactive learning media to help students better understand Pascal's Law through accurate visualization and hands-on experiments. Therefore, the development of Arduino Load Cell-based media is intended to offer an engaging and interactive learning experience to improve student comprehension of the material.